The Brunner’s Gland Lesions: An uncommon entity mimicking malignancy - Sarika More; Madhubala Swarnakar; Rajendra Kumar Chandrakar; Manjula Lader (Asian Journal of Medical Sciences, 2022)
Brunner’s gland hyperplasia (BGH) or adenoma is an uncommon benign lesion which mimics malignancy in the duodenum. In the present study, five cases of BGH were reported, out of which one case was presented with large size measuring 5.54×4.05 cm, which has not been yet reported. Computed tomography demonstrated a large obstructing polypoidal mass, on esophagogastroduodenoscopy demonstrated polypoidal growth, and histologic examination revealed brunner’s gland adenoma. Most of the cases presented with gastric outlet obstruction and upper gastrointestinal bleeding with other non-specific symptoms. BGH is an uncommon benign condition of the duodenum, patients were usually asymptomatic or may present with non-specific symptoms or present as an incidental finding on endoscopy. Endoscopic and/or surgical resection represents the ideal approach. Brunner’s gland described by the Swiss anatomist Johann Conrad Brunner in 1688, predominantly present within the submucosa, begin just distal to the gastroduodenal junction, and gradually decrease in size and number distally and are often used as a histological marker of the duodenum. A Brunner’s gland adenoma (BGA), also known as BGH or hamartoma, is an uncommon benign lesion in the duodenum.